Simultaneously boosting the conjugation, brightness and solubility of organic fluorophores by using AIEgens. Issue 32 (3rd August 2020) - Qi, Ji; Duan, Xingchen; Cai, Yuanjing; Jia, Shaorui; Chen, Chao; Zhao, Zheng; Li, Ying; Peng, Hui-Qing; Kwok, Ryan T. K.; Lam, Jacky W. Y.; Ding, Dan; Tang, Ben Zhong
Abstract : AIEgens are exploited to simultaneously extend the conjugation, boost the brightness, and increase the solubility of organic near-infrared fluorophores, representing a new strategy for developing high-performance emitters for biomedical imaging. Abstract : Organic near-infrared (NIR) emitters hold great promise for biomedical applications. Yet, most organic NIR fluorophores face the limitations of short emission wavelengths, low brightness, unsatisfactory processability, and the aggregation-caused quenching effect. Therefore, development of effective molecular design strategies to improve these important properties at the same time is a highly pursued topic, but very challenging. Herein, aggregation-induced emission luminogens (AIEgens) are employed as substituents to simultaneously extend the conjugation length, boost the fluorescence quantum yield, and increase the solubility of organic NIR fluorophores, being favourable for biological applications. A series of donor–acceptor type compounds with different substituent groups ( i.e., hydrogen, phenyl, and tetraphenylethene (TPE)) are synthesized and investigated. Compared to the other two analogs, MTPE-TP3 with TPE substituents exhibits the reddest fluorescence, highest brightness, and best solubility. Both the conjugated structure and twisted conformation of TPE groups endow the resulting compounds with improved fluorescence properties and processability for biomedical applications. The in vitro and in vivo applications reveal that the NIR nanoparticles function as a potent probe for tumour imaging. This study would provide new insights into the development of efficient building blocks for improving the performance of organic NIR emitters.